The Norwegian Pension Reform in 2011: The Long Term Impact on Take-up of Pension and Labor Supply - Erik Hernæs; Steinar Strøm; Tao Zhang (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate the impact on pension take-up and labour supply of a broad Norwegian pension reform. Focussing on the long term impact, we use a structural discrete choice model estimated on data for first groups to become eligible for the new pension, accounting for the opportunity cost of retiring early. A majority of the individuals combine take-up of pension with working. This is particular the case for individuals with lower education. The estimated model explains observed behaviour rather precisely, in particular for those who retire entirely and for all choices made by individuals with higher education. The estimated model is applied in an out of sample prediction for the cohort born in 1950. Again, the model predicts rather accurately the fraction that retires entirely and the choices made by the higher educated. Two policy simulations, an increase in longevity and tax on pension income equal to tax on labour income, implies lower take up of pensions and more people working. The response to the longevity adjustment compensates less than half of the reduction of the annual pension level in the adjustment, which is designed to mimic the increase in the longevity over the next 20 years.
Keywords: D10; H55; J26; 330; pension reform; labor supply